2020
DOI: 10.1111/1440-1681.13317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of B cell‐mediated PD‐1/PD‐L1 interaction in pancreatic cancer patients

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a common type of pancreatic cancer with one of the worst survival rate of all malignancies. Recent studies have identified that immunosuppressive B cells could employ the PD‐1/PD‐L1 pathway to suppress antitumour T cell responses; hence, we examined the expression and function of PD‐L1 in B cells. We found that the PD‐L1 expression was significantly enriched in tumour‐infiltrating (TI) B cells than in peripheral blood (PB) B cells from the same patients. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…PD-L1 is overexpressed in several solid human cancers, including PDAC, and represents an established mechanisms exploited by neoplastic cells to promote tumor escape from immune-surveillance ( 134 , 135 ). B-regulatory cells from patients with PDAC also express high levels of PD-L1 and in vitro interact with PD-1 expressing CD8 + T cells leading to reduced proliferation and IFN-γ secretion ( 131 , 136 ) ( Figure 2 ). Combined inhibition of IL-18 and PD-L1/PD-1 pathways with synthetic inhibitors reduces PDAC growth and metastasis formation in orthotopic animal models, reinforcing the in vivo relevance of the crosstalk between Breg and cancer cells for the progression of pancreatic cancer ( 130 ).…”
Section: Tumor Promoting Role Of B-lymphocytes In Pancreatic Adenocar...mentioning
confidence: 99%
“…PD-L1 is overexpressed in several solid human cancers, including PDAC, and represents an established mechanisms exploited by neoplastic cells to promote tumor escape from immune-surveillance ( 134 , 135 ). B-regulatory cells from patients with PDAC also express high levels of PD-L1 and in vitro interact with PD-1 expressing CD8 + T cells leading to reduced proliferation and IFN-γ secretion ( 131 , 136 ) ( Figure 2 ). Combined inhibition of IL-18 and PD-L1/PD-1 pathways with synthetic inhibitors reduces PDAC growth and metastasis formation in orthotopic animal models, reinforcing the in vivo relevance of the crosstalk between Breg and cancer cells for the progression of pancreatic cancer ( 130 ).…”
Section: Tumor Promoting Role Of B-lymphocytes In Pancreatic Adenocar...mentioning
confidence: 99%
“…In human PDAC samples, PDAC patients with higher B cell content in TME have significantly shorter survival ( 96 ). When constructing mouse models, we found that during this process, extensive infiltration of Bregs increased the expression of IL-1β and decreased the activity of CD8+ T cells, promoting tumorigenesis ( 97 ), while reverse expression of PD-L1 and IL-35 in Bregs supported immune escape of tumor cells ( 98 , 99 ). In addition, one of the characteristics of the occurrence and progression of PDAC is matrix reaction.…”
Section: Immunosuppressive Associated Cells During the Progression Of...mentioning
confidence: 99%
“…Recent work shows that B cells can be found in two main locations in PDAC [80] : 1-scattered infiltrating the tumor-stromal surface and 2-organized in ectopic lymph-node like structures called tertiary lymphoid tissue (TLT) [80] . After affinity maturation of CD20 + naïve B cells in the germinal centers of TLT, circulating plasmablasts are produced [81] . Those plasmablasts have been shown to be the most potent subset of B cells to stimulate collagen production by CAFs, and they show high expression of genes involved in fibroblast activation and proliferation, including the collagen genes COL1A1 and COL1A2, insulin-like growth factor-1 (IGF-1), and lysyl oxidase homolog 2 (LOXL2) [81] .…”
Section: B Cellsmentioning
confidence: 99%
“…After affinity maturation of CD20 + naïve B cells in the germinal centers of TLT, circulating plasmablasts are produced [81] . Those plasmablasts have been shown to be the most potent subset of B cells to stimulate collagen production by CAFs, and they show high expression of genes involved in fibroblast activation and proliferation, including the collagen genes COL1A1 and COL1A2, insulin-like growth factor-1 (IGF-1), and lysyl oxidase homolog 2 (LOXL2) [81] . A high density of B cells in TLT is associated with improved survival [80] .…”
Section: B Cellsmentioning
confidence: 99%